2017
DOI: 10.1186/s12888-017-1370-7
|View full text |Cite
|
Sign up to set email alerts
|

The comparative effectiveness and efficiency of cognitive behaviour therapy and generic counselling in the treatment of depression: evidence from the 2nd UK National Audit of psychological therapies

Abstract: BackgroundCognitive Behaviour Therapy (CBT) is the front-line psychological intervention for step 3 within UK psychological therapy services. Counselling is recommended only when other interventions have failed and its effectiveness has been questioned.MethodA secondary data analysis was conducted of data collected from 33,243 patients across 103 Improving Access to Psychological Therapies (IAPT) services as part of the second round of the National Audit of Psychological Therapies (NAPT). Initial analysis cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
66
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 25 publications
10
66
1
2
Order By: Relevance
“…Therefore, referring clients as a first line of treatment to therapies other than CBT should be considered, as research demonstrates they are as effective as CBT (e.g. Pybis, Saxon, Hill, & Barkham ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, referring clients as a first line of treatment to therapies other than CBT should be considered, as research demonstrates they are as effective as CBT (e.g. Pybis, Saxon, Hill, & Barkham ).…”
Section: Discussionmentioning
confidence: 99%
“…Practice-based studies comparing the effectiveness of psychological interventions reach similar conclusions. For example, a recent large-scale comparison of cognitive behavioural therapy (CBT) and person-centred counselling for depression (CfD) in primary care suggested that these treatments are equally effective (Pybis, Saxon, Hill, & Barkham, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…National Health Service services are locally commissioned and can vary. Recent research suggests that NHS site factors do have a significant impact on client outcomes, with some services markedly less effective than others, even after controlling for patient variables, therapy type and sessions attended (Pybis et al., ). The results of this study potentially suggest some of the factors that may explain the variable effectiveness of NHS psychological therapy services.…”
Section: Discussionmentioning
confidence: 99%